If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3 + -7y) + -1(6 + -3x) = 8 + -2y (3 * 4 + -7y * 4) + -1(6 + -3x) = 8 + -2y (12 + -28y) + -1(6 + -3x) = 8 + -2y 12 + -28y + (6 * -1 + -3x * -1) = 8 + -2y 12 + -28y + (-6 + 3x) = 8 + -2y Reorder the terms: 12 + -6 + 3x + -28y = 8 + -2y Combine like terms: 12 + -6 = 6 6 + 3x + -28y = 8 + -2y Solving 6 + 3x + -28y = 8 + -2y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + 3x + -6 + -28y = 8 + -6 + -2y Reorder the terms: 6 + -6 + 3x + -28y = 8 + -6 + -2y Combine like terms: 6 + -6 = 0 0 + 3x + -28y = 8 + -6 + -2y 3x + -28y = 8 + -6 + -2y Combine like terms: 8 + -6 = 2 3x + -28y = 2 + -2y Add '28y' to each side of the equation. 3x + -28y + 28y = 2 + -2y + 28y Combine like terms: -28y + 28y = 0 3x + 0 = 2 + -2y + 28y 3x = 2 + -2y + 28y Combine like terms: -2y + 28y = 26y 3x = 2 + 26y Divide each side by '3'. x = 0.6666666667 + 8.666666667y Simplifying x = 0.6666666667 + 8.666666667y
| 0=4+5 | | x+2/3+x+3/4=5 | | a+(a+2)+(a/3)=100 | | 3x/63 | | 5m-5m=-10+3-7 | | 3X+3X-4=14+X+7X | | 13x+2=-13(0)+2 | | 6x-(2x+3)=3x-10 | | 4(m-8)=4m | | 2(0.5x-4)=-(x-5) | | 2m+5=5m-35-3m | | 2/(y+2)+(3/y)=(-y)/(y+2) | | K(-5)=6-5+100 | | 2m-9=2m-16+7 | | Y=2x^2-7x-4 | | x/7+2x/9 | | 1/(3x)+(6x-9)/(3x)=(3x-3)/(4x) | | 3m+3-5=3m-2 | | us+uv=r | | 5/6p+3/4q=4 | | 6(y-7)=-6 | | 4Z-4=12Z+16 | | y^2-1/9 | | -4x+3*(-2x-5)=-3-6*(3x-4) | | 3/x-5+2/x+4=5/7 | | -2-3x=-x-6 | | 5x+134= | | 8d-d-4d-5-4d=0 | | 2senx+1=0 | | 9x+-27=45 | | 5x+134=2x+32 | | 8x-5*(4x+7)=2+4*(2x-3) |